Dominican Republic : 2015 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2016)
The Dominican Republic remains among the most dynamic economies in the region, benefiting from a strengthened macro-policy framework and external tailwinds. It does not face significant internal or external imbalances: inflation is low, fiscal deficits and debt moderate, and the external position is broadly in line with fundamentals. Vulnerabilities remain, however: public debt is set to increase over the medium-term and the tax ratio is one of the lowest in the world, reserves are below the Fund's suggested metric, legacy bottlenecks in the electricity sector remain unresolved, and social challenges persist. The consultations focused on policies to address these vulnerabilities and strengthen the economy's resilience to external shocks.